Factores que influyen en el incumplimiento del esquema de vacunación en niños menores de dos años, usuarios del Subcentro de Salud de Misahualli, provincia de Napo año 2013-2014 - Linares Ulloa, Mayra Jissela (2014)
The failure immunization scheme got investigate on mothers of child’s under two years old of the Misahualli health sub center users, because it has appear a big index of child that do not fulfill correctly with the scheme of vaccination, thence arouse the interest of the author on doing a nursing plan that motives the fulfillment and through a questionnaire that was implicated to the mothers the wished results was done. The investigation is; not experimental, fixed transverse, descriptive, bibliographic and by the place of camp. According to the results the we found out that the main causes were: the distance with a 70%, the economic situation with a 64%. It got concluded that 33 children corresponding to a 46% represent the accomplished of the scheme and won’t let the body create the antibodies require for the sickness. The displacement of the personal in the communities is required. A propose was created who containment was written in a manual that was given to the Mrs. coordinator of nursing in the Misahualli nursing sub center, at the same time it was sent to the TAPS (technical in primary attention), this manual focus to the importance of the fulfillment of the vaccination scheme, with purpose to contribute a better immunization cover. To realize this work titration we counted with the office material and information piques, Microsoft Word for the drafting of the text, Excel for the tabulation and presentation in graphics and pictures, Power Point was necessary for the exposition of the presentation of the work titration and diffusion of the personal manual of health and to the Misahualli sub centers users. Main words: Facts, Fulfillment, Scheme, Vaccination, Users, Children under two years old.